The 360 Leader : Developing Your Influence from Anywhere in the Organization - Maxwell, John C. (Nashville Thomas Nelson, 2005)
Is it possible to lead well when you're not the top dog? Leadership expert John C. Maxwell has a simple answer to this commonly-asked question: absolutely.
Keywords: Organization -- Executive ability -- Leadership